Renal Cell Carcinoma in von Hippel–Lindau Disease—From Tumor Genetics to Novel Therapeutic Strategies - Kim, Emily; Zschiedrich, Stefan (Frontiers in Pediatrics, 2018)
Von Hippel Lindau disease (VHL) is an autosomal dominant syndrome caused by mutations in the VHL tumor suppressor gene, leading to the dysregulation of many hypoxia-induced genes. Affected individuals are at increased risk of developing recurrent and bilateral kidney cysts and dysplastic lesions which may progress to clear cell renal cell carcinoma (ccRCC). Following the eponymous VHL gene inactivation, ccRCCs evolve through additional genetic alterations, resulting in both intratumor and intertumor heterogeneity. Genomic studies have identified frequent mutations in genes involved in epigenetic regulation and PI3K-AKT-mTOR pathway activation. Currently, local therapeutic options include nephron-sparing surgery and alternative ablative procedures. For advanced metastatic disease, systemic treatment, including inhibition of vascular endothelial growth factor (VEGF) pathways and mechanistic target of rapamycin (mTOR) pathways, as well as immunotherapy are available. Multimodal therapy, targeting multiple signaling pathways and/or enhancing the immune response, is currently being investigated. A deeper understanding of the fundamental biology of ccRCC development and progression, as well as the development of novel and targeted therapies will be accelerated by new preclinical models, which will greatly inform the search for clinical biomarkers for diagnosis, prognosis, and response to treatment.